Proinflammatory Cytokines in the Embolic Model of Cerebral Ischemia in Rat - Hamid Reza Jafarinaveh; Mohammad Allahtavakoli; Hossein Rezazadeh; Mohammad Kazemi Arababadi; Mohammad Mohsen Taghavi; Ali Shamsizadeh; Mohammad Reza Rahmani (Iranian Journal of Allergy, Asthma and Immunology, 2014)
Increased levels of proinflammatory cytokines have been recorded after the onset  of transient  or  permanent  brain  ischemia and  are  usually associated with  exacerbation  of ischemic injury. Embolic stroke model is more relevant to the pathophysiological situation in such  patients, because the  majority of  ischemic injuries in humans  are induced  by old thrombi that originate from the heart and carotid arteries. Therefore, the aim of the present study was to investigate changes of inflammatory cytokines after embolic stroke. Rats were subjected to embolic stroke, induced by a natural old clot which was injected in Middle Cerebral Artery (MCA), or  sham  stroke, which the  same volume of  saline was injected into the MCA. At 48 h after stroke induction, the levels of 5 cytokines (IL-1α and β, IL-6, IFN-γ and TNF-α) were determined in 500 µg of total protein using the Bio-Plex Rat Cytokine Array (BioRad), according to the manufacturer’s instructions in ischemic and non- ischemic cortices. While stroke animals showed infarctions and neurological deficits, we did not observe any cerebral infarction and neurological deficits in sham-operated animals. The levels of IL-1α (p=0.000) and -β (p =0.004), IL-6 (p =0.008), TNF-α (p =0.000) and IFN-γ (p =0.044) were significantly increased compared to sham treated animals. The findings of the present study suggest that part of ischemic injury in the embolic stroke may be mediated through the increased levels of inflammatory cytokines.